1990
DOI: 10.3171/jns.1990.72.1.0015
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating craniocerebral injuries in the Israeli involvement in the Lebanese conflict, 1982–1985

Abstract: From June, 1982, through June, 1985, 113 patients were evacuated to Rambam Maimonides Medical Center with penetrating craniocerebral injuries sustained in ongoing military hostilities in Lebanon. Two factors distinguished this group of patients from those presenting in earlier conflicts: 1) this was the first large series in which computerized tomography (CT) was routinely used to initially evaluate combat head injuries; and 2) in an effort to preserve maximum cerebral tissue, intracranial debridement was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
0
6

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(116 citation statements)
references
References 17 publications
6
103
0
6
Order By: Relevance
“…Outcomes were similar to Vietnam-era patient series and most interestingly, long-term incidence of postoperative seizures or infection due to retained fragments was low. 8 A similar conclusion was obtained from a large series of patients suffering from low-velocity penetrating head injuries in the Iran-Iraq conflict.…”
Section: Current Treatmentsupporting
confidence: 60%
See 1 more Smart Citation
“…Outcomes were similar to Vietnam-era patient series and most interestingly, long-term incidence of postoperative seizures or infection due to retained fragments was low. 8 A similar conclusion was obtained from a large series of patients suffering from low-velocity penetrating head injuries in the Iran-Iraq conflict.…”
Section: Current Treatmentsupporting
confidence: 60%
“…Although Hammon 36,37 echoed the need for aggressive debridement based on his large series from the Vietnam War, other studies since that time have shown the benefits of a more limited debridement. 8 In particular, Brandvold et al 8 studied 113 patients in Israel during the Lebanese conflict from 1982 to 1985. With the advent of CT imaging, a less aggressive surgical debridement was studied in which patients underwent initial simple debridement with no specific effort to remove indriven bone or metal fragments identified on CT unless easily accessible by gentle irrigation.…”
Section: Current Treatmentmentioning
confidence: 99%
“…17) Recently, the suggested treatment for missile or shrapnel head wounds has been divided into four groups: Large craniotomy or craniectomy and aggressive deep debridement, no surgical operation, minimal or superficial debridement, and simple debridement of the entrance gutter through a small craniotomy. 6,10,15,33,40) There is no consensus about the surgical indications or aggressiveness because of the great number of variables to be considered, such as the number and distribution of fragments, the occurrence of different types of lesions caused by different types of missiles and shrapnel particles, and the involvement of eloquent areas. Only superficial debridement of the entrance gutter and closure of the wound has been suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Based on epidemiologic studies on civilian or military populations, most of which were conducted before modern imaging era, the risk factors for PTE include old age, penetrating injuries, injury severity (GCS<10), biparietal or multiple contusions, intracranial hemorrhage, frontal or temporal location of the lesion, >5 mm brain midline shift, duration of coma >24 h, loss of consciousness >24 h, prolonged length of posttraumatic amnesia, multiple intracranial procedures, and the occurrence of early post-traumatic seizures [10,[12][13][14][15][16][17]. Related to methodology, many of the identified risk factors directly or indirectly reflect the severity of brain injury, and strengthen the view that the risk for PTE increases with the severity of TBI.…”
Section: Process Of Epileptogenesis In Humansmentioning
confidence: 99%